Intestinal Secretory Immunoglobulin A Response to Enteroaggregative Escherichia coli in Travelers with Diarrhea - Sutjita, Made (American Society for Microbiology, 2000)
We examined stool samples from travelers for secretory immunoglobulin A (sIgA) to enteroaggregative Escherichia coli (EAEC) during episodes of acute diarrhea. Ten paired samples from 10 patients with diarrhea caused by EAEC were examined for the presence of specific sIgA by dot blot and Western blot immunoassays. Five samples were positive by dot blotting, and two samples were positive by Western blotting.